Characterization of the antiproliferative signal mediated by the somatostatin receptor subtype sst5 - Cordelier, Pierre (The National Academy of Sciences of the USA, 1997)
We investigated cell proliferation modulated by cholecystokinin (CCK) and somatostatin analogue RC-160 in CHO cells bearing endogenous CCK(A) receptors and stably transfected by human subtype sst5 somatostatin receptor. CCK stimulated cell proliferation of CHO cells. This effect was suppressed by inhibitor of the soluble guanylate cyclase, LY 83583, the inhibitor of the cGMP dependent kinases, KT 5823, and the inhibitor of mitogen-activated protein (MAP) kinase kinase, PD 98059. CCK treatment induced an increase of intracellular cGMP concentrations, but concomitant addition of LY 83583 virtually suppressed this increase. CCK also activated both phosphorylation and activity of p42-MAP kinase; these effects were inhibited by KT 5823. All the effects of CCK depended on a pertussis toxin-dependent G protein. Somatostatin analogue RC-160 inhibited CCK-induced stimulation of cell proliferation but it did not potentiate the suppressive effect of the inhibitors LY 83583 and KT 5823. RC-160 inhibited both CCK-induced intracellular cGMP formation as well as activation of p42-MAP kinase phosphorylation and activity. This inhibitory effect was observed at doses of RC-160 similar to those necessary to occupy the sst5 recombinant receptor and to inhibit CCK-induced cell proliferation. We conclude that, in CHO cells, the proliferation and the MAP kinase signaling cascade depend on a cGMP-dependent pathway. These effects are positively regulated by CCK and negatively influenced by RC-160, interacting through CCK(A) and sst5 receptors, respectively. These studies provide a characterization of the antiproliferative signal mediated by sst5 receptor.